Tindak Tutur Ilokusi Asertif dalam Bahasa Melayu Dialek Kabupaten Kuantan Singingi, Riau: Penelitian - Ghina’a Jayanthi Putri; Charlina; Aprini Harsalina; Salsabila Ramadhani Putri; Anggun Sridifa; Selvi Anggraini; Nadia Dwi Putri; Nursafitri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study discusses speech acts in the Malay dialect of Kuantan Singingi Regency, Riau Province, based on Searlee's theory. Speech acts are an important aspect in pragmatics that influence communication. This study uses a qualitative descriptive method to analyze local community conversation data. The results of the study indicate that there are five categories of speech acts, namely assertive, directive, commissive, expressive, and declarative. This study specifically discusses assertive illocutionary speech acts. This study also reveals the relationship between language, culture, and place.